2019
DOI: 10.1186/s12940-019-0519-x
|View full text |Cite
|
Sign up to set email alerts
|

Methodological limitations in experimental studies on symptom development in individuals with idiopathic environmental intolerance attributed to electromagnetic fields (IEI-EMF) – a systematic review

Abstract: BackgroundHypersensitivity to electromagnetic fields (EMF) is a controversial condition. While individuals with idiopathic environmental intolerance attributed to electromagnetic fields (IEI-EMF) claim to experience health complaints upon EMF exposure, many experimental studies have found no convincing evidence for a physical relation. The aim of this systematic review was to evaluate methodological limitations in experimental studies on symptom development in IEI-EMF individuals that might have fostered false… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 83 publications
0
23
0
3
Order By: Relevance
“…Conducting tests on an individual level is recommended [Schmiedchen et al, 2019] but requires a higher number of repetitions of real or sham exposure sessions and a higher time investment from the participants. Most participants expressed their willingness to take part in a sufficient number of tests to obtain a sufficiently high statistical power at the individual level provided that they were able to perceive the EMF exposure.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Conducting tests on an individual level is recommended [Schmiedchen et al, 2019] but requires a higher number of repetitions of real or sham exposure sessions and a higher time investment from the participants. Most participants expressed their willingness to take part in a sufficient number of tests to obtain a sufficiently high statistical power at the individual level provided that they were able to perceive the EMF exposure.…”
Section: Resultsmentioning
confidence: 99%
“…The hypothesis of an electromagnetic origin of such symptoms has been widely investigated by provocation studies, which consist of deliberately exposing people with IEI‐EMF to particular EMF sources in laboratory settings to observe the volunteers’ reactions. In the majority of studies, these reactions have been found to be independent of exposure: people with IEI‐EMF did not perceive EMF beyond chance, did not get more symptoms during real rather than sham exposures [Rubin et al, 2010; Schmiedchen et al, 2019], and did not react physiologically (heart rate variability, skin conductivity, cognitive functioning, etc.) differently to real and sham exposure [Rubin et al, 2011; Andrianome et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations